Stemness and clinical features in relation to the subventricular zone in diffuse lower-grade glioma: an exploratory study. Issue 1 (4th June 2022) - Corell, Alba; Gómez Vecchio, Tomás; Ferreyra Vega, Sandra; Dénes, Anna; Neimantaite, Alice; Hagerius, Alexander; Barchéus, Hanna; Solheim, Ole; Lindskog, Cecilia; Bontell, Thomas Olsson; Carén, Helena; Jakola, Asgeir S; et al.
Abstract: Background: The subventricular zone (SVZ) of the human brain is a site of adult stem cell proliferation and a microenvironment for neural stem cells (NSCs). It has been suggested that NSCs in the SVZ are potential cells of origin containing driver mutations of glioblastoma, but their role in the origin of diffuse lower-grade gliomas (dLGGs) is not much studied. Methods: We included 188 patients ≥18 years with IDH -mutated dLGG (WHO grades 2–3) histologically diagnosed between 2007 and 2020. Tissue microarrays of tumor samples for patients between 2007 and 2016 were used for immunodetection of Nestin, SOX2, SOX9, KLF4, NANOG, CD133 cMYC, and Ki67. DNA methylation profile was used for stemness index (mDNAsi). Tumor contact with the SVZ was assessed and the distance was computed. Results: Overall, 70.2% of the dLGG had SVZ contact. Tumors with SVZ contact were larger (102.4 vs 30.9 mL, P < .01), the patients were older (44.3 vs 40.4 years, P = .04) and more often had symptoms related to increased intracranial pressure (31.8% vs 7.1%, P < .01). The expression of SOX2, SOX9, Nestin, and Ki67 showed intersample variability, but no difference was found between tumors with or without SVZ contact, nor with the actual distance to the SVZ. mDNAsi was similar between groups ( P = .42). Conclusions: We found no statistical relationship between proximity with the SVZ and mDNAsi or expression of SOX2, SOX9, Nestin, and Ki67 in IDH -mutated dLGG. Our data suggest that the potential impact of SVZ on IDH -mutated dLGG is probably not associated with a more stemness-like tumor profile.